‘Luxuries of the mind’: Contextualising Art Photography, Eroticism and History of Medicine in the Social tableaux vivants of Lejaren à Hiller's Sutures in Ancient Surgery (1920s–1940s) - Connor, J. T. H. (Transactions of the Royal Historical Society, 2024)
In 1927 Lejaren à Hiller (1880–1969) produced a series of black and white art photographs entitled Sutures in Ancient Surgery evoking scenes from the distant past of surgery and medicine. Commissioned and distributed in North America by Davis & Geck, Inc. to promote sales of its surgical sutures (stitches), several depictions were erotic owing to the centrality and poses of nude female models. The first series appeared as ads in professional technical journals, then as packets assembled in paper portfolios distributed to doctors who were primarily men. The creation of Hiller's oeuvre in different forms over almost a century – journal advertisement, portfolio, book, exhibit, magazine features and textbook illustration – highlights his enduring broad appeal, although his work has since been subject to criticism because of its perceived sexism. At its root, Sutures was an advertising medium that connected a seller to a potential buyer. The content and presentation of the project also connected medicine present with medicine past, which also may have helped physicians to connect with the then blossoming field of medical history. The appeal Sutures may have had for a past male medical culture would not resonate with the more gender-inclusive and less overtly sexist medical profession of today, which also prompts discussion of the associations across art, obscenity, medicine and society. My reassessment of Hiller's work based on analysis of his artwork, contemporary interviews, published critiques, Hiller's own writings and DG company records extends previous analyses as it is more comprehensive in scope and also considers more fully works by Hiller antecedent to Sutures that probably greatly influenced it, such as photopoetry books, other advertising projects and his silent movie films.